PCR APPROACH FOR RAPID DETECTION OF Escherichia coli IN TEMPE USING A SPECIFIC PRIMER - Siti Harnina Bintari; Fidia Fibriana; Dewi Mustikaningtyas; Retno Sri Iswari (The East Java Biological Society, 2014)
Tempe known as a traditional fermented food originated from Indonesia. It has a unique flavour and texture. It also contains high protein and usually serves to substitute meat, fish, or egg as a complement to rice. The manufacture process of Tempe is quite complex and mostly, the traditional process has not employed the hygienic standard. In the process of Tempe making, there are two critical stages of the whole process; i.e. soaking of soybeans and solid state fermentation by Rhizopus sp. During the process, foodborne pathogen bacteria such as Escherichia coli could contaminate the product of Tempe. The bacterial contamination could be revealed through culture dependent methods which is costly, laborious, and time consuming. Therefore, the culture-independent method such as polymerase chain reaction using a specific primer could be applied to detect target microorganism to save time and labour. In this study, thirty-one Tempe samples collected from different manufacturers in Semarang, Central Java, Indonesia were analysed by PCR. In order to obtain the bacterial genomic DNA, a modified Chelex 100-Microwave method was employed. The results of DNA extraction showed that the method was an applicable method. It gave high quantity and quality of DNA; therefore, it could be applied in the PCR reaction. The DNA samples were employed in PCR for detection of Escherichia coli using Ecoli706F/R. It was found that 27 out of 31 samples were detected having Escherichia coli contamination showed by the presence of the amplified product size 706 bp. The application of this method could significantly reduce costs and time of analysis in the laboratory. Further response after E. coli were detected could be employed, including investigation of the critical factors in Tempe manufacturing process which allowed E. coli contamination.